Self‐Management Behaviors in Relation to Psychological Factors and Interdialytic Weight Gain Among Patients Undergoing Hemodialysis in Indonesia. Issue 4 (18th February 2019) - Natashia, Dhea; Yen, Miaofen; Chen, Hsing‐Mei; Fetzer, Susan J.
Abstract: Purpose: The purpose of this study was to understand the influence of demographic and psychological factors on self‐management behaviors and interdialytic weight gain (IDWG) as a fluid adherence marker among patients undergoing hemodialysis in Indonesia. Design: A quantitative correlational study. Method: A convenience sample of 145 patients undergoing hemodialysis was recruited from the dialysis units in two hospitals in Jakarta from September to December 2015. Questionnaires were used to examine self‐management behaviors, depression, anxiety, and stress. Data for IDWG were obtained by subtracting the individual's predialysis weight from his or her postdialysis weight from the previous session. Hierarchical multiple linear regression identified the predictors of IDWG. Results: Self‐advocacy was ranked the least performed self‐management behavior, while medication adherence was ranked the most likely to be performed. Among the subscales of the Self‐Management Behavior Indices, positive correlations were found between the communication dimension with all psychological factors (depression, anxiety, and stress), while self‐advocacy had positive correlation with anxiety. Subjects gained a mean of 4.5% of their postdialysis weight, with over 50% exceeding the recommended 4% IDWG. Overall, 53.6% of the IDWG was explained by the weekly duration of hemodialysis, level of depression, communication, partnership in care, and self‐advocacy. Conclusions: Self‐management behaviors are potential predictors that can be modified by nephrology nurses in order to enhance clinical outcomes, with the specific outcome being IDWG. Self‐management behaviors contribute to the promotion of appropriate IDWG. Depressed patients are less likely to adhere to weight gain restrictions. Clinical Relevance: Education combined with training in self‐management behaviors—particularly communication, becoming a partner in care, and advocating for care—may improve adherence to IDWG guidelines among Indonesian hemodialysis patients. Interventions targeting depressed patients are needed.